Helicobacter pylori babA2, cagA, and s1 vacA genes work synergistically in causing intestinal metaplasia. Issue 4 (1st April 2003) - Zambon, C-F; Navaglia, F; Basso, D; Rugge, M; Plebani, M
Abstract : Aims: To determine any associations between the Helicobacter pylori genes babA2, oipA, cagA and the s and m alleles of vacA. In addition, to verify whether these genes work synergistically or independently in causing gastritis, peptic ulcer, and intestinal metaplasia. Methods: One hundred and sixty seven H pylori positive patients were studied (52 antral gastritis, 41 diffuse gastritis, 41 peptic ulcer, and 33 duodenitis). Helicobacter pylori virulence genes were amplified by means of the polymerase chain reaction. Results: Significant associations were found between babA2 and the other H pylori genes studied. When considered singly, all the genes were associated with disease diagnosis, inflammation, and intestinal metaplasia. Four H pylori groups were defined. Group A: cagA−, s2m2, babA2−; group B: cagA+, s1m1, babA2+; group C: cagA+, s1m2, babA2+; group D: cagA+, s1m2, babA2−. Group A infecting strains were associated with less severe endoscopic and inflammatory conditions, whereas group B strains were associated with the worst endoscopic and inflammatory findings. Intestinal metaplasia was a rare finding in group A infected patients (< 10%), whereas it was frequent in those infected with group B strains (48%). Conclusions: The H pylori genes cagA, oipA "on", s1 and m1 vacA, and babA2 are associated with each other, possibly as a result of shared selective pressure. When coexpressed by the same H pylori strain, cagA, s1 and m1 vacA, and babA2 work synergistically in worsening inflammation. Infections caused by strains coexpressing cagA, s1m1 vacA, and babA2 are those at higher risk for intestinal metaplasia.